Pengukuran Interleukin-6 (IL-6), C-Reactive Protein (CRP) dan D-Dimer sebagai prediktor prognosis pada pasien COVID-19 gejala berat: sebuah tinjauan pustaka - I Ketut Wardika; I Gusti Putu Hery Sikesa (Intisari Sains Medis, 2021)
Background: Patients with severe symptoms of Coronavirus disease-19 (COVID-19) experience a cytokine storm and coagulopathy that contribute to increased mortality requires a clinical parameter that is useful for risk stratification of COVID-19 patients. This literature review will discuss further the role of measuring D-Dimer, CRP and IL-6 levels as predictors of severe COVID-19 symptoms and prognostic predictors in severe COVID-19 patients.Methods: This literature review involved the relevant literature on CRP, IL-6, D-dimer and COVID-19. Different data sources or manual literature search methods were used to search for articles related to the literature topic.Results: In COVID-19, severe hyperinflammatory response cytokine storm symptoms were characterized by the release of excessive proinflammatory cytokines such as IL-6 and an increase in CRP as an acute phase reactant. In addition, there is also a coagulopathy condition which is characterized by an increase in D-dimer. There were significant differences in CRP, IL-6 and D-dimer levels between COVID-19 patients with mild and severe symptoms. levels of CRP, IL-6 and D-dimer also showed a significant relationship with increased severity and mortalityConclusion: Measurement of CRP, IL-6 and D-dimer levels is useful for predicting the occurrence of severe COVID-19 symptoms and a prognostic predictor in patients with severe COVID-19 symptoms. Latar Belakang: Pasien Coronavirus disease-19 (COVID-19)  gejala berat mengalami badai sitokin dan koagulopati yang berkontribusi terhadap tingginya angka mortalitas. Diperlukan suatu parameter klinis yang berguna untuk stratifikasi risiko pasien COVID-19. Tinjauan pustaka ini akan membahas lebih lanjut mengenai peran pengukuran kadar D-Dimer, CRP dan IL-6 sebagai prediktor terjadinya COVID-19 gejala berat dan prediktor prognostik pada pasien COVID-19 gejala berat.Metode: Tinjauan pustaka ini melibatkan literatur yang relevan tentang CRP, IL-6, D-dimer dan COVID-19. Sumber data yang berbeda atau metode pencarian literatur manual digunakan untuk mencari artikel yang berkaitan dengan topik literatur.Hasil: Pada infeksi COVID-19 gejala berat terjadi badai sitokin akibat respon hiperinflamasi ditandai dengan dilepasnya sitokin pro-inflamasi berlebih seperti IL-6 serta peningkatan CRP sebagai reaktan fase akut. Selain itu terjadi pula kondisi koagulopati yang ditandai dengan peningkatan D-dimer. Terdapat perbedaan kadar CRP, IL-6 dan D-dimer yang signfikan antara pasien COVID-19 dengan gejala ringan dan gejala berat. Peningkatan kadar CRP, IL-6 dan D-dimer juga menunjukkan hubungan signifikan dengan peningkatan keparahan infeksi serta mortalitasSimpulan: Pengukuran kadar CRP, IL-6 dan D-dimer bermanfaat sebagai prediktor terjadinya COVID-19 gejala berat dan prediktor prognostik pada pasien COVID-19 gejala berat.